2000
DOI: 10.4049/jimmunol.165.1.322
|View full text |Cite
|
Sign up to set email alerts
|

Tapasin-Mediated Retention and Optimization of Peptide Ligands During the Assembly of Class I Molecules

Abstract: The murine class I H-2Kb molecule achieves high level surface expression in tapasin-deficient 721.220 human cells. Compared with their behavior in wild-type cells, Kb molecules expressed on 721.220 cells are more receptive to exogenous peptide, undergo more rapid surface decay, and fail to form macromolecular peptide loading complexes. As a result, they are rapidly transported to the cell surface, reflecting a failure of endoplasmic reticulum retention mechanisms in the absence of loading complex formation. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
84
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 53 publications
8
84
1
1
Order By: Relevance
“…Much of the work examining tapasin function has understandably been performed using either tapasin-deficient cells (6,8,(40)(41)(42)(43)(44)(45) or mutant MHC class I molecules that no longer associate with tapasin (13,14,16,23,25). However, in tapasin-deficient cells, it is now apparent that TAPBPR is present and still capable of binding to MHC class I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the work examining tapasin function has understandably been performed using either tapasin-deficient cells (6,8,(40)(41)(42)(43)(44)(45) or mutant MHC class I molecules that no longer associate with tapasin (13,14,16,23,25). However, in tapasin-deficient cells, it is now apparent that TAPBPR is present and still capable of binding to MHC class I.…”
Section: Discussionmentioning
confidence: 99%
“…Tapasin simultaneously binds to peptide-receptive MHC class I heterodimers and to TAP, localizing MHC class I to a concentrated source of newly degraded antigenic peptides (1)(2)(3)(4)(5). There is also evidence that tapasin optimizes or edits the peptides presented on MHC class I by facilitating exchange of suboptimal peptides for higher-affinity cargo (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…3A). Various groups have suggested that tapasin retains empty or poorly loaded (and therefore unstable) MHC-I molecules in the ER until proper peptide loading is accomplished (29,33). In the absence of tapasin, a greater proportion of K b molecules that reach post-Golgi compartments (including the cell surface) may be poorly loaded and unstable.…”
Section: Alternate Mhc-i Ag Processing Involves Post-golgi Mhc-i Molementioning
confidence: 99%
“…Tapasin is complexed with calreticulin, MHC-I-␀ 2 -microglobulin, and TAP, and is necessary for association of TAP with the other components of this peptide loading complex (24,25). In addition to promoting assembly of the MHC-I peptide loading complex, tapasin has been suggested to help retain MHC-I molecules in the ER until they are loaded with high affinity peptides (25)(26)(27)(28)(29)(30)(31)(32). Recently, tapasin ÏȘ/ÏȘ mice were described (33,34).…”
Section: Onventional Class I Mhc (Mhc-i)mentioning
confidence: 99%
“…Tapasin bridges heavy chain-␀ 2 m heterodimers to TAP (Sadasivan et al, 1996) and thus provides physical proximity between MHC class I molecules and TAP. Tapasin also retains MHC class I molecules in the ER (Schoenhals et al, 1999;Barnden et al, 2000;Grandea et al, 2000), which might enhance peptide loading. In addition, tapasin optimizes the repertoire of bound peptides to achieve maximal affinity of the interaction (Garbi et al, 2000;Myers et al, 2000;Tan et al, 2002;Williams et al, 2002b;Howarth et al, 2004;Elliott and Williams, 2005).…”
mentioning
confidence: 99%